Нейромережева система керування електрогідроциклоном - Дудник, А.О.; Штепа, В.М.; Лисенко, В. П. (Energy and Automation, 2017)
NEURAL NETWORK CONTROL SYSTEM OF ELECTROHYDROCYCLONEA. Dudnyk, V.Shtepa, V. LysenkoAnnotation. The results of research of electrohydrocyclone mode, which is used for water purification are shown. Neural network control system of electrohydrocyclone  as well as its hardware and software was developed.Keywords: electrotechnical complex, electrohydrocyclone, water treatment, neural network